Controlled deterioration test for evaluation of sunn hemp seed vigor - Silva, Arthur Batoqui Costa E; Galvão, Ícaro Monteiro; Barbosa, Rafael Marani; Silva, Clíssia Barboza Da; Vieira, Roberval Daiton (ABRATES - Associação Brasileira de Tecnologia de Sementes, 2015)
The controlled deterioration test is efficient for seed vigor evaluation of several species. However, the procedures conditions are incipient, especially in respect to tropical forages such as sunn hemp, which still does not have a standardized procedure. The objective of this research was to adjust the procedures for a controlled deterioration test in Crotalaria juncea L. seeds. For this, five commercial seed lots were evaluated for water content and initial physiological potential (germination test, first germination count, germination speed index, saturated salt accelerated aging with NaCl, electrical conductivity and seedling field emergence). For controlled deterioration test, the initial seed moisture content was adjusted to 18, 21 and 24% and, subsequently, the samples were exposed at 45 °C during 24 hours. Seed germination test was conducted with the use of sand as substrate. Evaluations were performed on the fourth, fifth and sixth day after sowing. The controlled deterioration test for sunn hemp seeds should be performed with 24% seed moisture content, at 45 °C during 24 hours, and the test evaluation on the fourth day after sowing.

Resumo O teste de deterioração controlada é eficiente para avaliar o vigor de sementes de diversas espécies. No entanto, as condições para realização desse teste são incipientes, principalmente quando se trata de forrageiras tropicais, como é o caso da crotalária, cujas informações sobre a adequação do teste ainda são escassas. Assim, o objetivo deste trabalho foi adequar os procedimentos para a execução do teste de deterioração controlada para sementes de Crotalaria juncea L. Para tanto, cinco lotes de sementes comerciais foram avaliados quanto ao teor de água e potencial fisiológico inicial (teste de germinação, primeira contagem, índice de velocidade de germinação, envelhecimento acelerado com solução saturada de NaCl, condutividade elétrica e emergência de plântulas em campo). Para o teste de deterioração controlada, o teor de água inicial das sementes foi ajustado para 18, 21 e 24% e, posteriormente, as amostras foram expostas a 45 °C durante 24 horas, postas para germinar entre areia, e avaliadas aos quarto, quinto e sexto dias após a semeadura. O teste de deterioração controlada em crotalária deve ser conduzido com sementes contendo 24% de teor de água, a 45 °C, durante 24 horas e a leitura realizada aos quatro dias após a semeadura.
Teste de deterioração controlada para avaliação do vigor de sementes de crotalária
Keywords: Crotalaria juncea L.; germination; physiological potential; test standardization; Crotalaria juncea L.; germinação; potencial fisiológico; padronização de teste